The Kurdish migrants in Yenibosna: "social exclusion", class and politics - Kanzık, Alp. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
This study is based upon a group of forced Kurdish migrants whose "social exclusion" is generally suggested to have arrived at an extent in which the forced migrants are both out of the labor market and grassroots politics. This thesis basically suggests the opposite: the forced migrants fill the ranks of the informal labor market to a significant extent and, at the same time, they constitute the main actors of grassroots politics within the urban slum. The “new urban poverty” approach, on the other hand, suggests that social exclusion has arrived to an extent that absolute disconnection from economic, social and political life is at hand and that the risk of “underclass” is imminent. Building upon a mainly qualilative research conducted in the district of Yenibosna, located in the borough of Bahçelievler in Istanbul, this thesis criticizes this approach along mainly (but not exclusively) two lines. While acknowledging the basic premises of the “new urban poverty” regime and the inevitability of “social exclusion”, this thesis shows that the Kurdish migrants are not really excluded from the labor market at all: more or less regularly employed within the textile sector over long periods of time, the Kurdish migrants form a forcibly dispossessed or proletarianized population which occupies the lower ranks of the urban informal labor market. In other words, exclusion results not from “absolute disconnection” per se but from their “integration” as cheap labor into the labor market. Furthermore, their community has not disappeared; a total atomization has not taken place. Their relationship with the state is, on the other hand, not to be understood in a basic dichotomy of presence or lack; rather, it turns out to be more ambiguous. Lastly, the Kurdish migrants, politically mobilized to a large extent, turn out to be inside grassroots politics. Given these assumptions, could we speak of a “class formation” rather than a “class deformation”, this thesis basically asks in the last instance. The answer is affirmative. What is at hand is a class in formation, a significant portion of which is formed by the Kurdish forced migrants whose exclusion should not suggest that they are out of the market and politics at all. The actors of grassroots politics have, after all, shifted towards the Kurdish migrants. Thus, if one is to speak of politics and class in the urban slum or of informality or policies against exclusion, this cannot overlook or underestimate the existence and politics of the forced migrants, this thesis basically suggests.
Keywords: Marginality, Social.